VIEWS OF INDONESIAN STUDENTS ON TRANSLATION THEORY CLASS: A CASE STUDY - Suwarni Wijaya Halim (E-LINK JOURNAL, 2022)
In any practical field, tensions always exist between the group that views theoretical study as necessary and those who consider it pointless: likewise in the case of translation. Translation often places most of its emphasis on its practical aspects. The theoretical aspect of translation is often marginalized in professional settings. Nevertheless, in the context of translator training, translation theory is as an essential area, which needs to be studied and explored. This study investigated the views of 5th- and 7th-semester students of English Department at a private undergraduate educational institution in Jakarta, Indonesia, on translation theory. The class Theory of Translation is the only official locus for instruction in theories of translation at the target institution. The results of this study may provide several benefits, including the aiding the creation of syllabuses for and teaching translation theory. The author used a questionnaire to acquire the data needed to address the research questions. The results of this research revealed that most students in the 5th and 7th semester of English study in Jakarta, Indonesia, have a positive perception of translation theory, believing that it is essential for translation practice. Moreover, they also considered that translation theory could provide solutions for issues in the practice of translation.